Touch : building your brand in the experience economy - Dietzel, Jörg, 1961- (Marshall Cavendish Business, 2020)
From online to offline, events to Instagram: Experiences matter. Consumer Researchers have called experiences ""the new luxury"". So what does that mean for brands, established or new? How do you create a seamless brand experience across all touchpoints, one that transforms customers into brand advocates who are telling your story? Brand consultant and university lecturer Jörg Dietzel writes the playbook for creating brand experiences - based on over 30 years of experience working with blue chip clients in Europe, the United States and Asia. The book is illustrated by case studies drawn from t